The international law of human trafficking - Gallagher, Anne T. (Cambridge Univ. Press, 2010)
The international legal definition -- The international legal framework -- Specific legal issues -- State responsibility for trafficking -- Obligations of protection and support -- Obligations related to repatriation and remedies -- Obligations of an effective criminal justice response -- Obligations to prevent trafficking and respond lawfully -- Issues of compliance, implementation, and effectiveness